Role of aryl hydrocarbon receptors in infection and inflammation - Xu, Linglan; Lin, Luping; Xie, Nan; Chen, Weiwei; Nong, Weihua; Li, Ranhui (Frontiers in Immunology, 2024)
The aryl hydrocarbon receptor (AhR) is a transcription factor that is activated by various ligands, including pollutants, microorganisms, and metabolic substances. It is expressed extensively in pulmonary and intestinal epithelial cells, where it contributes to barrier defense. The expression of AhR is pivotal in regulating the inflammatory response to microorganisms. However, dysregulated AhR expression can result in endocrine disorders, leading to immunotoxicity and potentially promoting the development of carcinoma. This review focuses on the crucial role of the AhR in facilitating and limiting the proliferation of pathogens, specifically in relation to the host cell type and the species of etiological agents involved in microbial pathogen infections. The activation of AhR is enhanced through the IDO1-AhR-IDO1 positive feedback loop, which is manipulated by viruses. AhR primarily promotes the infection of SARS-CoV-2 by inducing the expression of angiotensin-converting enzyme 2 (ACE2) and the secretion of pro-inflammatory cytokines. AhR also plays a significant role in regulating various types of T-cells, including CD4 + T cells and CD8 + T cells, in the context of pulmonary infections. The AhR pathway plays a crucial role in regulating immune responses within the respiratory and intestinal barriers when they are invaded by viruses, bacteria, parasites, and fungi. Additionally, we propose that targeting the agonist and antagonist of AhR signaling pathways could serve as a promising therapeutic approach for combating pathogen infections, especially in light of the growing prevalence of drug resistance to multiple antibiotics.